IN VITRO SCREENING OF THE LEAVES OF MUSA PARADISIACA FOR ANTHELMINTIC ACTIVITY - A. Hussain.; M. N. Khan; M. S. Sajid; Z. Iqbal; M. K. Khan; R. Z. Abbas; M. A. Raza; G. R. Needham (Journal of Animal and Plant Sciences, 2010)
Helminthosis is one of the major problems of livestock production throughout the world, particularly in tropical and subtropical areas. Chemical control of helminths is in practice in most of the parts of the world. The problem of the development of resistance against the common chemical anthelmintics has renewed the interest in the study of medicinal plants for the development of novel anthelmintics. The present study has been planned to evaluate ovicidal efficacy of Musa paradisiaca leaves, used locally for worm control in sheep. For this purpose, egg hatch test (EHT) was conducted on nematodes ova to investigate the in vitro ovicidal effects of crude aqueous (CAE) and crude aqueous-methanol extracts (CAME) of the leaves of the plant. Lethal concentration 50 (LC50) values of CAE and CAME of Musa paradisiaca leaves were 0.0207 and 0.4813, respectively. This study shows that Musa paradisiaca leaves possess in vitro anthelmintic activity. The study also suggests further large scale pharmacological and toxicological studies for their safer use in veterinary medicine.
Keywords: anthelmintic; gastrointestinal nematodes; Musa paradisiaca; sheep